2021
DOI: 10.17269/s41997-021-00474-y
|View full text |Cite|
|
Sign up to set email alerts
|

Rising burden of multimorbidity and related socio-demographic factors: a repeated cross-sectional study of Ontarians

Abstract: Objective This study aimed to provide population-level data regarding trends in multimorbidity over 13 years. Methods We linked provincial health administrative data in Ontario, Canada, to create 3 cross-sectional panels of residents of any age in 2003, 2009, and 2016 to describe: (i) 13-year trends in multimorbidity prevalence and constellations among residents and across age, sex, and income; and (ii) chronic condition clusters. Multimorbidity was defined as having at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 41 publications
1
34
0
1
Order By: Relevance
“…Finally, multimorbidity has been associated with low area-level income among Ontario residents. 41,42 Although we found that net costs for COVID-19 increased linearly with higher ADG comorbidity score, they were similar across income and marginalization measures.…”
Section: Marginalization and Structural Risk Factorsmentioning
confidence: 58%
“…Finally, multimorbidity has been associated with low area-level income among Ontario residents. 41,42 Although we found that net costs for COVID-19 increased linearly with higher ADG comorbidity score, they were similar across income and marginalization measures.…”
Section: Marginalization and Structural Risk Factorsmentioning
confidence: 58%
“…High hospital bed occupancy inhibits emergency department (ED) throughput and has a direct downstream impact on the quality and timeliness of emergency care provided [ 2 ]. Hospital inpatient units have become increasingly congested and overburdened alongside increased patient complexity and occupancy loads [ 3 , 4 ]. Ontario’s number of in-patient hospital beds have remained relatively the same over the past decade; the lowest of all Canadian provinces when measured in beds per capita (1.4 per 1000) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Comorbidities included 18 chronic conditions (acute myocardial infarction, arrhythmia, asthma, cancer, congestive heart failure, chronic obstructive pulmonary disease, coronary artery disease, dementia, diabetes, hypertension, in ammatory bowel disease, non-psychotic mood and anxiety disorders, other mental health illnesses, osteoarthritis, osteoporosis, renal disease, rheumatoid arthritis, and stroke) with high prevalence and economic burden in Ontario. (40)(41)(42) OCR data were used for tumor location and cancer staging (43)(44)(45) to derive the "best stage" grouping consistent with the American Joint Committee on Cancer staging manual(46). Residence was de ned as rural (community size greater than 10,000 persons) or urban using postal codes in the RPDB, and income quintile as the median income of a patient's postal code using Canadian census data (47,48).…”
Section: Covariatesmentioning
confidence: 99%